Chromatin Binding of c-REL and p65 Is Not Limiting for Macrophage IL12B Transcription During Immediate Suppression by Ovarian Carcinoma Ascites - Unger, Annika; Finkernagel, Florian; Hoffmann, Nathalie; Neuhaus, Felix; Joos, Barbara; Nist, Andrea; Stiewe, Thorsten; Visekruna, Alexander; Wagner, Uwe; Reinartz, Silke; Müller-Brüsselbach, Sabine; Müller, Rolf; et al. (Frontiers in Immunology, 2018)
Tumors frequently exploit homeostatic mechanisms that suppress expression of IL-12, a central mediator of inflammatory and anti-tumor responses. The p40 subunit of the IL-12 heterodimer, encoded by IL12B, is limiting for these functions. Ovarian carcinoma patients frequently produce ascites which exerts immunosuppression by means of soluble factors. The NFκB pathway is necessary for transcription of IL12B, which is not expressed in macrophages freshly isolated from ascites. This raises the possibility that ascites prevents IL12B expression by perturbing NFκB binding to chromatin. Here, we show that ascites-mediated suppression of IL12B induction by LPS plus IFNγ in primary human macrophages is rapid, and that suppression can be reversible after ascites withdrawal. Nuclear translocation of the NFκB transcription factors c-REL and p65 was strongly reduced by ascites. Surprisingly, however, their binding to the IL12B locus and to CXCL10, a second NFκB target gene, was unaltered, and the induction of CXCL10 transcription was not suppressed by ascites. These findings indicate that, despite its reduced nuclear translocation, NFκB function is not generally impaired by ascites, suggesting that ascites-borne signals target additional pathways to suppress IL12B induction. Consistent with these data, IL-10, a clinically relevant constituent of ascites and negative regulator of NFκB translocation, only partially recapitulated IL12B suppression by ascites. Finally, restoration of a defective IL-12 response by appropriate culture conditions was observed only in macrophages from a subset of donors, which may have important implications for the understanding of patient-specific immune responses.